Discontinuing Factors in Foreign Language Learning: The Case of Malaysian Undergraduate Learners - Rokiah, Paee; Kai-Chee, Lam; Najwa Hanani, KOPLI; Wee-Ling, Kuan (2021)
This cross-sectional study attempts to identify factors affecting the beginner learners of Mandarin and Japanese as a foreign language from continuing their learning to the higher level at one public university in Malaysia. To answer the research question, this study employed web-based online survey and semi- structured interview as a means of data collection. The participants of this study are homogeneous, where it is restricted to undergraduate learners who has taken Japanese or Mandarin level 1 but did not proceed to level 2, which is the next level at the same university. A total of 44 learners responded to the online survey and 10 were interviewed. From their responses, the researchers identified four main factors: (1) Coping with the class, (2) Self-accomplishment, (3) Schedule, and (4) Peer. The data also revealed that although the learners did not proceed to the next level, their interest towards the language remains and some are planning to further their learning in the next semester or even after graduating. The study concludes with implications for enhancing the teaching of Japanese and Mandarin in similar contexts.